Lung cancer CT screening: Psychological responses in the presence and absence of pulmonary nodules. (October 2018) - Clark, Marcia E.; Bedford, Laura E.; Young, Ben; Robertson, John F.R.; das Nair, Roshan; Vedhara, Kavita; Littleford, Roberta; Sullivan, Francis M.; Mair, Frances S.; Schembri, Stuart; Rauchhaus, Petra; Kendrick, Denise
Highlights: Pulmonary nodules are commonly found on CT scans screening for lung cancer (LC). Some non-UK studies show negative psychological impacts of pulmonary nodule diagnosis. We explored psychological impacts of nodule diagnosis during LC screening in the UK. There was little impact on affect, health anxiety, worry, illness perception or risk perception. There were fewer short-term avoidance symptoms in those diagnosed with nodules. Abstract: Objectives: To determine the psychological response (thoughts, perceptions and affect) to a diagnosis of pulmonary nodules following a novel antibody blood test and computed tomography (CT) scans within a UK population. Materials and methods: This study was nested within a randomised controlled trial of a blood test (Early CDT®-Lung test), followed by a chest x-ray and serial CT-scanning of those with a positive blood test for early detection of lung cancer (ECLS Study). Trial participants with a positive Early CDT®-Lung test were invited to participate (n = 338) and those agreeing completed questionnaires assessing psychological outcomes at 1, 3 and 6 months following trial recruitment. Responses of individuals with pulmonary nodules on their first CT scan were compared to those without (classified as normal CT) at 3 and 6 months follow-up using random effects regression models to account for multiple observations per participant, with loge transformation of data where modelling assumptions were not met. Results: There were no statistically significant differences between the nodule and normal CT groups in affect, lung cancer worry, health anxiety, illness perceptions, lung cancer risk perception or intrusive thoughts at 3 or 6 months post-recruitment. The nodule group had statistically significantly fewer avoidance symptoms compared to the normal CT group at 3 months (impact of events scale avoidance (IES-A) difference between means −1.99, 95%CI −4.18, 0.21) than at 6 months (IES-A difference between means 0.88, 95%CI −1.32, 3.08; p-value for change over time = 0.003) with similar findings using loge transformed data. Conclusion: A diagnosis of pulmonary nodules following an Early CDT®-Lung test and CT scan did not appear to result in adverse psychological responses compared to those with a normal CT scan.